Time Course of Changes in Extravascular Water of the Lung After Pneumonectomy According to the Data of Transpulmonal Thermodilution - V. V. Kuzkov; Ye. V. Suborov; V. N. Kuklin; M. Sobkhez; M. Yu. Kirov; L. Ya. Bjertnes (Общая реаниматология)
Objective: to study the accuracy of pulmonary extravascular water (PEVW) measurement by thermochromodilution (TCD) and isolated thermodilution (ITD) on a model of pneumonectomy and subsequent ventilator-induced lung lesion (VILL) in sheep.Materials and methods: the study was conducted at the Research Laboratory of University of Tromse. The experiment included 12 sheep weighing 35.6±4.6 kg. Thoracotomy and right-sided pneumonectomy were performed in the animals under general anesthesia and controlled artificial ventilation. After measurement of the parameters of systemic hemodynamics and PEVW, the animals were divided into 2 groups: 1) 1) those undergoing protective ventilation (PV, n=6) with a tidal volume (TV) of 6 ml/kg and a positive end-expiratory pressure (PEEP) of 2 cm H2O and 2) those with VILL (n=6) with a TV of 12 ml/kg and a PEEP of 0 cm H2O. TCD and ITD (Cold Z-021 and PiCCOplus monitors, respectively (Pulsion, Germany)) were used to measure volumetric parameters and PEVW. The parameters of pulmonary hemodynamics, respiratory mechanics, and blood gas composition were recorded. After euthanasia of the animals, their lungs were taken to determine the control value of PEVW by postmortem gravimetry (PG).Results: in the VILL group, significant pulmonary alveolar edema developed, which was followed by hyperthermia, elevated pulmonary pressure, and increased intrapulmonary shunting. Analysis of the data indicated a close correlation between the PEVW values obtained by TCD and ITD with PG (r=0.95 and r=0.81, respectively; p<0.01; n=12). The PG deviation was 0.57±2.05 and 2.68±3.61 ml/kg for TCD and ITD, respectively (M±2d, p<0.05).Conclusion: both used techniques have an acceptable accuracy and adequately reflect both a reduction in PEVW after pneumectomy and its increase in the presence of VILL. Volumotrauma may be the key factor that provokes the development of postpneumectomic edema of the lung.